Smart Farming- Drip Irrigation Controlled using LR-WPAN with hybrid Power - sagala, albert; Sitompul, Janasde; Hutauruk, Joel; Sitorus, Riado (Jurnal Sistem Informasi dan Ilmu Komputer, 2022)
Agricultural sectors always need technology to get higher yields. Wireless Sensor Technology with LR-WPAN gives the opportunity to control the plat with minimum cost. In this paper, we developed a system that optimally waters agricultural crops based on a wireless sensor network technology. The scope in this paper consists of two main components: a hybrid power source and a communication system between end nodes with the gateway. The first component was designed and implemented in control box hardware using PLC (Programmable Logic Controller) to generate the power to all components (microcontroller, sensor, and actuator). The second is transmission data from end node to gateway by utilizing Zigbee protocol. The automation uses data from three soil moisture sensors as a trigger to the ON/OFF solenoid valve for watering the field. It may conclude that the system can work properly, the data from the field was sent real-time. Also, the hybrid power was working properly to supply power.